2008
DOI: 10.1007/s10717-009-9101-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the conditions of hydrolysis of tetraethoxysilane on the synthesis of forsterite

Abstract: The sol-gel process for synthesizing forsterite from magnesium acetate and tetraethoxysilane (TEOS) is investigated. The effect of the conditions of hydrolysis of TEOS on the morphology and phase composition of the powders is studied. It is found that a solution of magnesium acetate and TEOS hydrolysate in an acid medium forms a stable sol which transforms into gel. In this case, the yield of forsterite after heat-treatment at 800°C is 97%. Performing hydrolysis in an alkaline medium and combining the hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Magnesium acetate tetrahydrate is widely used as the precursor for the synthesis of magnesium oxide and magnesium containing oxides in the forms of thin film, rode, porous particles with high specific surface area, and so on, where ethanol-mediated sol–gel process and subsequent thermal decomposition of the as-prepared gel are the major chemical processes. For example, Bian et al reported a successful template-free synthesis of mesoporous magnesium oxide via the thermal decomposition of monodispersive crystalline particles of anhydrous magnesium acetate for the application in carbon dioxide adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium acetate tetrahydrate is widely used as the precursor for the synthesis of magnesium oxide and magnesium containing oxides in the forms of thin film, rode, porous particles with high specific surface area, and so on, where ethanol-mediated sol–gel process and subsequent thermal decomposition of the as-prepared gel are the major chemical processes. For example, Bian et al reported a successful template-free synthesis of mesoporous magnesium oxide via the thermal decomposition of monodispersive crystalline particles of anhydrous magnesium acetate for the application in carbon dioxide adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the intensity of the magnesia reflections has been increased and, more importantly, the forsterite peaks have disappeared in comparison to Fig. 2, suggesting a more silicon depletion and lack. Considering the promoting role of water in both hydrolysis and condensation sol-gel reactions [30,31], even with the presence of water in the HCl solution used for this exaggerated sample, any improvement in the expected calcined structure was not only achieved, but also the deviation with respect to the expected stoichiometry was enhanced. It suggests the domination of the inhibiting role of HCl and verifies the above described mechanism about condensation inhibited by the severe chelation effect.…”
Section: Resultsmentioning
confidence: 97%
“…Для синтеза форстерита разработаны различные методы подготовки порошков, такие как соосаждение, золь-гель, твердофазная реакция, метод саморастекания и т. д. [6][7][8][9]. Но керамика, полученная на основе порошков, синтезированных указанными выше способами, всегда имеет некоторые ограничения по плотности и механической прочности, которые необходимы для материалов, применяемых в высокотемпературных условиях.…”
Section: вв шеховцов нк скрипникова оа кунц вестник тгасу 2023 т 25 №unclassified